Bulimia from the Perspective of Persian Medicine (PM) - Fatemeh Nojavan; Narges Tajik (Journal of Research on History of Medicine)
Eating disorders are debilitating, life-threatening, and costly mental disorders that significantly impair physical health and adversely affect psychosocial functioning. Nowadays, six main feeding and eating disorders are identified in diagnostic systems, and Bulimia nervosa is one of them. The aim of this paper is twofold: First, it seeks to shed light on the concept of bulimia as understood by the Persian school of medicine. This study has attempted to consider the roots of this disease within this tradition. It will compare the concept of bulimia nervosa in conventional medicine with that of Canine appetite disease in Persian medicine in the Islamic Golden Era (9th-12th centuries). Secondly, it will analyze and show the evolution of the term bulimia throughout history. For this purpose, Avicenna’s Canon of Medicine, primary PM resources, and important databases were reviewed using the related keywords. Although these diseases are in the category of emerging mental illness, evidence suggests that its roots can be found in Persian medicine. The comparison made between the definition of Canine appetite in this school and modern definitions of Bulimia nervosa shows striking similarities between the two diseases, suggesting that both are the same disease.